Penatalaksanaan Holistik pada Perempuan Usia 60 Tahun dengan Diabetes Mellitus Tipe 2 melalui Pendekatan Kedokteran Keluarga - Sonia Anggraini; Aila Karyus (CV. Jasa Sukses Abadi, 2021)
Diabetes Mellitus (DM) is a global public health problems, in 2014 the prevalence of DM sufferers reached 9% of the world's total population and 90% of them are DM type 2. The mortality rate for DM disease in 2012 worldwide reached 1.5 million. In 2013, the International Diabetes Federation (IDF) estimated there were 382 million people with DM in the world. Family approach in the management of diabetes mellitus helps identify factors that influence both clinical, personal and psychosocial family. This study is intended as the application of family doctor services to patients by identifying risk factors, clinical problems, and patient management based on a patient's problem-solving framework with a patient centered and family approach. This is a case report study. Primary data were collected by history, physical examination, examinations and home visits to assess the physical environment. A 60 years old woman diagnosed with type 2 diabetes mellitus with lacking knowledge of the disease, curative treatment behaviour, poor diet, rarely exercising and low physical activity and low family knowledge about diabetes mellitus. After the intervention, the patient has shown clinical improvement and changes in behavior towards the patient's disease. In the quantitative assessment, there is an increase in all aspects assessed which are knowledge, diet and physical activity. Management of diabetes mellitus patients holistically and comprehensively, patient center, family approach with diabetes mellitus treatment is needed in order to prevent acute and advanced complications.